Incipient speciation in Drosophila melanogaster involves chemical signals. - Grillet, M.; Everaerts, C.; Houot, B.; Ritchie, M.G.; Cobb, M.; Ferveur, J.F. (Scientific reports, 2012)
The sensory and genetic bases of incipient speciation between strains of Drosophila melanogaster from Zimbabwe and those from elsewhere are unknown. We studied mating behaviour between eight strains - six from Zimbabwe, together with two cosmopolitan strains. The Zimbabwe strains showed significant sexual isolation when paired with cosmopolitan males, due to Zimbabwe females discriminating against these males. Our results show that flies' cuticular hydrocarbons (CHs) were involved in this sexual isolation, but that visual and acoustic signals were not. The mating frequency of Zimbabwe females was highly significantly negatively correlated with the male's relative amount of 7-tricosene (%7-T), while the mating of cosmopolitan females was positively correlated with %7-T. Variation in transcription levels of two hydrocarbon-determining genes, desat1 and desat2, did not correlate with the observed mating patterns. Our study represents a step forward in our understanding of the sensory processes involved in this classic case of incipient speciation.